Ökotopia - Multidimensional cities need multidimensional data. - Frantz, Hans-Georg (My University, 2014)
The development of a multidimensional criteria catalog brings along data for the evaluation of the actual situation for cities or areas in cities. The criteria are defined in four research groups in the area of social living, building, energy and transport. The criteria are defined by different indicators weighted due to their importance. The indicators themselves are described by values, which depend on the approachableness of sustainability. The data from the criteria catalog is available for specific applications or services for townplaners either from authorities or planning offices or the commercial developers of areas.
Keywords: Stadtplanung; Stadtökologie; Datenerfassung; Planungsgrundlage; Zustandserfassung; Evaluation; Kriterienkatalog; Klimadaten; Sozialökologie; Smart City